Architecture respecting the place - Wrana, Jan (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
An architect undertaking some creative activity ‘’today”, touches ‘’the future”, and tomorrow our interference directed towards ‘’the future” will be nothing else but ‘’the past”. Therefore, while thinking about architecture as a constant cultural message concerning the place, the architect-creator is obliged to collect and analyse the research material in order to take accurate project decisions. Nowadays, after the thorough analysis of research material, treating the result of our creative activities as a spatial message, we expect social allowance and acceptance for proposing new expressive forms, which create the processed message codes.